Random iterates of monotone maps - Rabi Bhattacharya; Mukul Majumdar (Cornell University, Center for Analytical Economics (CAE), 2008)
In this paper we prove the existence,uniqueness and stability of the invariant distribution of a random dynamical system in which the admissible family of laws of motion consists of monotone maps from a closed subset of a finite dimensional Euclidean space into itself.
Keywords: 330; Dynamisches Modell; Markovscher Prozess; Dynamische Optimierung; Theorie